2019
DOI: 10.1016/j.chb.2019.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Is cyberloafing more complex than we originally thought? Cyberloafing as a coping response to workplace aggression exposure

Abstract: Employees spend approximately two hours per day engaging in cyberloafing (i.e., using the internet at work for nonwork purposes) behaviors, costing organizations almost $85 billion dollars per year. As a result, cyberloafing is often considered a counterproductive type of withdrawal behavior. However, recent research suggests that cyberloafing may have some unexpected positive workplace outcomes. Therefore, we argue that the role of workplace cyberloafing is more complex than previously assumed and posit that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
85
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 44 publications
(52 reference statements)
10
85
0
7
Order By: Relevance
“…The results showed that perceived organizational support had an important role in increasing cyberloafing behavior. These findings have explained the general strain theory (Andel et al, 2019;Koay, 2018;Koay & Soh, 2018;Koay et al, 2017;Sawitri, 2012) of violations of organizational regulations by employees. The government provides support in the form of internet facilities to support the smooth running of work.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…The results showed that perceived organizational support had an important role in increasing cyberloafing behavior. These findings have explained the general strain theory (Andel et al, 2019;Koay, 2018;Koay & Soh, 2018;Koay et al, 2017;Sawitri, 2012) of violations of organizational regulations by employees. The government provides support in the form of internet facilities to support the smooth running of work.…”
Section: Resultssupporting
confidence: 52%
“…This is because there are negative sensations that cause tension on employees, so that employee involvement in cyberloafing behavior becomes the main strategy to alleviate these tensions. This opinion is supported by several studies that state that in reducing work stress, employees do cyberloafing (Andel et al, 2019;Koay, 2018;Koay & Soh, 2018;Koay et al, 2017;Sawitri, 2012).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…New forms of behavior are emerging related to the use of gadgets, which need scientific study and evaluation. These include fabbing (Krukova & Ekimchik, 2019) and cyberloafing (Andel, Kessler, Pindek, Kleinman, & Spector, 2019).…”
Section: Introductionmentioning
confidence: 99%